A Comparison Study of Kinta Valley Limestone and Gomantong Limestone: Mineralogy and Economic Potentiality - a/l Etiapan, Sivaraj (Universiti Teknologi PETRONAS, 2016)
Paleozoic limestone of Kinta Valley, Tapah and Cenozoic limestone of Gomantong Formation, Sabah were investigated to evaluate their mineralogy and texture and to decide their economic potentiality. Petrography study were performed to check the grain distribution and cementing properties and samples from both areas were powdered for X-Ray Fluorescence (XRF) to check the mineral content and for whiteness test. Thin section was used to compare the grain distribution and cementation properties with link to the whiteness and yellowness in the brightness test and also with trace elements from XRF. XRF, thin section and whiteness results shows that Kinta Valley limestone has a higher economic value compared to Gomantong Formation limestone. This can be concluded due to the very high and constant value of the carbonate content whereas trace elements content such as Mg, Si is relatively low compared to Gomantong Formation. It can be concluded that Gomantong Formation limestone which is of a low quality rock where it is feasible for a low value industrial usage such as building materials and slabs while Kinta Valley limestone shows a good quality of rocks for a higher value of industrial usage such as for iron and glass industry.